ANALYSIS OF THE MAGNETOHYDRODYNAMICS NANOVISCOUS FLUID BASED ON VOLUME FRACTION AND THERMOPHYSICAL PROPERTIES - Norasia, Yolanda; Tafrikan, Mohamad; Kamaluddin, Bhamakerti Hafiz (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Fluid flow control is applied in engineering and industry using computational fluid dynamics. Based on density, fluids are divided into two parts, namely non-viscous fluids and viscous fluids. Nanofluid is a fluid that has non-viscous and viscous characteristics. Nanoviscos fluid flow is interesting to study by considering the effect of volume fraction and thermophysical properties. Nanoviscous fluid flow models form dimensional equations that are then simplified into dimensionless equations. Dimensionless equations are converted into non-similar equations using flow functions and non-similar variables. Nanoviscous fluids with Cu particles and water-based fluids have higher temperatures and faster velocity. Based on the effect of volume fraction, the velocity of the nanoviscous fluid moves slower, while the temperature of the nanoviscous fluid increases.